Роль державних та недержавних інституцій у відновлені екосистем реінтегрованих територій - Yashchenko, G. A. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
The paper highlights the key role of non-state actors in ecosystem restoration through community mobilization, adaptive initiatives, and integration of local knowledge. It examines the relationship between ecological restoration and the Sustainable Development Goals, particularly in the context of biodiversity conservation, food security, and climate action. It examines challenges, including high unemployment, security risks, and political instability, that affect the effectiveness of restoration efforts. It highlights the importance of collaboration between state and non-state actors to achieve sustainable outcomes.